Model penentuan biaya long-term care dengan menggunakan anuitas joint life - Nurul Anisha Dahlan; Sri Dewi Anugrawati; Wahyuni Abidin (Papanda Publisher, 2026)
The increasing life expectancy in Indonesia has led to a growing elderly population, thereby intensifying the demand for financial protection against Long-Term Care (LTC) risks. This study aims to calculate the Actuarial Present Value (APV) of Long-Term Care (LTC) benefits for married couples using an actuarial model based on a multistate Markov framework. The model incorporates 15 possible health status transitions between the couple, covering combinations of healthy, ill, and deceased states without distinguishing between husband and wife. Transition probabilities are derived from the Indonesian Mortality Table IV (TMI IV) and the National Morbidity Table. These probabilities are then used to estimate the present value of LTC costs under assumptions of basic benefits, increased benefits when one or both spouses are ill, and a fixed interest rate of 6%. Simulation results show that the total present value of LTC benefits over a 20-year contract period amounts to IDR 96,537,664.69. This model demonstrates both flexibility and accuracy in estimating future care needs and the benefits received. The findings provide valuable insight for the design of spouse-based life insurance products in Indonesia